Sekolah Minggu Sebagai Sarana dalam Membentuk Iman dan Karakter Anak - Hadi Siswoyo (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
Sunday school is church organization formed to teach children about Christianity. With the material given, hopefully, children will grow by faith and have better character and become someone who has strong faith in God. Family’s role, especially parents’, is so important in educating and supporting children’s growth in faith and character. Although, it can not be denied that a complete education facility consists of four essential pillars. First, family where parents are the main source of character education for children. Second, church that religiously will help in forming children character. Third, government that protects children’s right legally. Fourth, environment in general.